2007
DOI: 10.1038/nm1543
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of methylarginine metabolism impairs vascular homeostasis

Abstract: There was an error published in J. Cell Sci. 120, 929-942. We apologise for the incorrect publication of a reference, for which the wrong year, title and journal details were given. The correct reference is shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
393
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(419 citation statements)
references
References 21 publications
19
393
4
3
Order By: Relevance
“…Numerous studies have demonstrated that overexpression of DDAH1 promotes angiogenesis in vitro and increases glioma growth in vivo through enhanced expression of NO and VEGF (Kostourou et al ., 2002; Smith et al ., 2003; Wojciak‐Stothard et al ., 2007). DDAH1 also plays a vital role in early embryogenesis (Breckenridge et al ., 2010; Leiper et al ., 2007). More recently, a study has shown that DDAH1 can inhibit the renal fibrosis process via the Wnt/β‐catenin pathway (Liu et al ., 2016), a well‐established crucial signaling event associated with a number of human diseases (Miao et al ., 2013; Miki et al ., 2011; de Sousa et al ., 2011) including cancer (Ramachandran et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that overexpression of DDAH1 promotes angiogenesis in vitro and increases glioma growth in vivo through enhanced expression of NO and VEGF (Kostourou et al ., 2002; Smith et al ., 2003; Wojciak‐Stothard et al ., 2007). DDAH1 also plays a vital role in early embryogenesis (Breckenridge et al ., 2010; Leiper et al ., 2007). More recently, a study has shown that DDAH1 can inhibit the renal fibrosis process via the Wnt/β‐catenin pathway (Liu et al ., 2016), a well‐established crucial signaling event associated with a number of human diseases (Miao et al ., 2013; Miki et al ., 2011; de Sousa et al ., 2011) including cancer (Ramachandran et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…NO is mainly produced by endothelial NO synthase (eNOS) and endothelial dysfunction is characterized by a loss of NO bioavailability. Impairment of eNOS activity by endogenous inhibitors such as asymmetrical dimethylarginine (ADMA) in endothelial dysfunction-associated diseases has gained interest (Leiper et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, elevated ADMA levels have been associated with all established cardiovascular risk factors (38). Furthermore, recent data from genetic mouse models indicate a causal role for ADMA in the pathophysiology of vascular disease (7,19). ADMA derives from the posttranslational methylation of L-arginine residues within proteins catalyzed by enzymes called protein arginine methyltransferases (PRMTs).…”
mentioning
confidence: 99%